Pengaruh Citra Perusahaan dan Lokasi Terhadap Keputusan Berkunjung di Pasar Tradisional Curug Agung Padalarang - Binsar Julius Santoso; Ajat Sudrajat (Peneliti.net, 2022)
This study aims to examine and analyze the influence of corporate image and location on the decision to visit the Curug Agung Padalarang Traditional Market. This study uses quantitative methods with descriptive and verification approaches. Popularity in this study was taken from the estimated number of visitors to the Curug Agung Padalarang Traditional Market in one year which amounted to 425,280 people, using Isaac and Michael's formula to determine the number of samples, the results obtained were 385 people/respondent. The sampling technique used is Accidental Sampling. This study uses bright scale analysis techniques and path analysis with SPSS 16 and Microsoft Excel 2019 data processing software. The results of this study indicate that there is a strong correlation between corporate image and location with a coefficient value of 0.743. Company image has a partial effect of 34.5% and location has a partial effect of 52.3%. Then the location has a greater influence on the Visiting Decision. Simultaneously Company Image and Location have an effect on Visiting Decisions with the magnitude of the effect being 86.8% while the remaining 13.2% is influenced by other variables not examined in this study. Keyword : Coorporate Image, Location, and Visit Decision